DIMENSI KERAHMATAN DALAM KAJIAN ILMU DAKWAH - Rodiyah Rodiyah (Institut Agama Islam Negeri Bengkulu, 2017)
Dakwah is an important thing in Islam, therefore between da’wah and Islam have an inseparable relationship. Islam as the religion of rahmatanlil’alamin needs to be done seriously to realize the values of the mercy in Islam in a more concrete form. Da’wah other than known as the process of delivering Islamic teachings also need to be understood that da’wah is also a process of application and actualization of Islamic teachings in a more real form to be perceived by every Muslim, and it can be realized in da’wah activities in the form of tadbir and tathwir.